Synoptic Oscillations of Arabian Anticyclones in the transition season - RAMAMURTHI, K. M.; KESHAVAMURTY, R. N. (MAUSAM, 1964)
In this paper, an attempt has been made to study the significant circulation features over the Arabian Sea characterizing the summer transition and the onset of southwest monsoon relation rains along the West Coast of India in two contrasting years. It was found that the more important feature on the was the sudden northward shift of the Arabian Sea sub-tropical anticyclone and its establishment over. West Pakistan and the adjoining areas of Iran particularly at the 300-mb level. At the 500-mb level, in addition to similar changes the monsoon trough also forms over the Malabar Coast simultaneously. A study of the moments of the subtropical anticyclones over the Arabian Sea and Africa during May 1963 at 300-mb level shows that these are displaced meridionally under the influence of troughs in westerlies the maximum equatorward displacement taking place when troughs move to a more southerly latitude. A more northerly position of the Arabian Sea anticyclone in April or early May appears to be associated with early commencement of the monsoon rains over Kerala.